Aged rhesus monkeys: Cognitive performance categorizations and preclinical drug testing. (1st April 2021) - Plagenhoef, Marc R.; Callahan, Patrick M.; Beck, Wayne D.; Blake, David T.; Terry, Alvin V.
Abstract: Rodent models have facilitated major discoveries in neurobiology, however, the low success rate of novel medications in clinical trials have led to questions about their translational value in neuropsychiatric drug development research. For age-related disorders of cognition such as Alzheimer' disease (AD) there is interest in moving beyond transgenic amyloid-β and/or tau-expressing rodent models and focusing more on natural aging and dissociating "healthy" from "pathological" aging to identify new therapeutic targets and treatments. In complex disorders such as AD, it can also be argued that animals with closer neurobiology to humans (e.g., nonhuman primates) should be employed more often particularly in the later phases of drug development. The purpose of the work described here was to evaluate the cognitive capabilities of rhesus monkeys across a wide range of ages in different delayed response tasks, a computerized delayed match to sample (DMTS) task and a manual delayed match to position (DMTP) task. Based on specific performance criteria and comparisons to younger subjects, the older subjects were generally less proficient, however, some performed as well as young subjects, while other aged subjects were markedly impaired. Accordingly, the older subjects could be categorized as aged "cognitively-unimpaired" or aged "cognitively-impaired" with a third group (aged-other) falling in between. Finally, as a proof of principle, we demonstrated using the DMTP task that aged cognitively-impaired monkeys are sensitive to the pro-cognitive effects of a nicotinic acetylcholine receptor (nAChR) partial agonist, encenicline, suggesting that nAChR ligands remain viable as potential treatments for age-related disorders of cognition. Highlights: There is a need for more translational studies in neuroscience drug discovery. Here, working memory was evaluated in rhesus monkeys with two behavioral tasks. Monkeys were categorized as aged, cognitively impaired and unimpaired. The nicotinic agonist encenicline improved memory in cognitively impaired monkeys.